UPN “Veteran” East Java’s Strategy in Creating Students with a National Defense Character - Pasya Ramadhani Delina Swartama; Sri Wibawani (Journal of Governance and Social Policy, 2026)
This study aims to analyse and describe the strategy of UPN “Veteran” East Java in realising the appearance of students with national defence character as part of the implementation of the university's vision of "Global Competitiveness with National Defence Character". Student appearance on campus is not only understood as a physical aspect but also as a representation of the values ​​of discipline, compliance with norms, and internalisation of national defence values ​​based on Pancasila and the 1945 Constitution. This study uses a qualitative approach with a descriptive research type. Data collection was carried out through in-depth interviews, observation, and documentation of informants consisting of student affairs leaders, national defense program managers, lecturers, and students. Data analysis uses an interactive model that includes data reduction, data presentation, and conclusion drawing. Framework analysis uses strategic management stages, namely the preparation strategy, implementation strategy, and evaluation strategy. The results of the study indicate that the institution's strategy in realizing the appearance of students with national defense character is carried out through formal regulations (Rector's Regulation on the student code of ethics), integration of national defense values ​​in the curriculum and student activities, continuous coaching and socialization, as well as monitoring and evaluation mechanisms. This strategy fosters consistent, neat, and disciplined student appearance, reflecting the character of national defense. Thus, student appearance becomes part of the institutional strategy to continuously strengthen the campus' national defense identity.